The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7150/ijbs.18649
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Regulation of Gene Expression by the Apoptosis- and Splicing-Associated Protein Complex and Its Components

Abstract: The differential deposition of RNA-binding proteins (RBPs) on pre-mRNA mediates the processes of gene expression. One of the complexes containing RBPs that play a crucial part in RNA metabolism is the apoptosis-and splicing-associated protein (ASAP) complex. In this review, we present a summary of the structure of ASAP complex and its localization. Also, we discuss the findings by different groups on various functions of the subunits of the ASAP complex in RNA metabolism. The subunits of the ASAP complex are R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 120 publications
(173 reference statements)
1
27
0
Order By: Relevance
“…In our study, all core proteins of a conserved ASAP complex, SR45, SAP18, and ACINUS, exhibited a significantly lower level of accumulation in the sr45-1 mutant. Their orthology to the ASAP complex proteins in animal models, shown here through amino acid sequence homology and predicted protein domain structures ( Supplemental Figures S2 and S3 ), supports the hypothesis that SR45 not only functions as a splicing regulator to affect pre-mRNA splicing, but can influence transcriptional control via associations with other proteins that are not splicing factors (Song and Galbraith, 2006; Hill et al, 2008; Zhang and Mount, 2009; Day et al, 2012; Xing et al, 2015; Questa et al, 2016; Deka and Singh, 2017; Zhang et al, 2017). Such an example is its interaction with SAP18 in the ASAP complex.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study, all core proteins of a conserved ASAP complex, SR45, SAP18, and ACINUS, exhibited a significantly lower level of accumulation in the sr45-1 mutant. Their orthology to the ASAP complex proteins in animal models, shown here through amino acid sequence homology and predicted protein domain structures ( Supplemental Figures S2 and S3 ), supports the hypothesis that SR45 not only functions as a splicing regulator to affect pre-mRNA splicing, but can influence transcriptional control via associations with other proteins that are not splicing factors (Song and Galbraith, 2006; Hill et al, 2008; Zhang and Mount, 2009; Day et al, 2012; Xing et al, 2015; Questa et al, 2016; Deka and Singh, 2017; Zhang et al, 2017). Such an example is its interaction with SAP18 in the ASAP complex.…”
Section: Discussionsupporting
confidence: 73%
“…SR45, an RNA-binding protein, is orthologous to RNPS1 in humans and other animals (Zhang and Mount, 2009). RNPS1 is a component of the apoptosis and splicing-associated protein (ASAP) complex (Schwerk et al, 2003), which functions to regulate RNA metabolism at multiple levels (Deka and Singh, 2017). The two other core proteins in the ASAP complex are SAP18 and ACINUS (Schwerk et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Acin1-L, Acin1-S , and Acin1-S' transcripts are transcribed from the Acin1 gene through alternative promoter usage or an AS mechanism [46] . All Acin1 isoforms share an RNA recognition motif, RSB domain, and RS-rich region within its C-terminus, whereas the N-terminal SAP motif within Acin1-L mediates its interaction with AT-rich DNA regions [47 , 48] . Proteomic assays indicated the nuclear distribution of the Acin1-S and Acin1-S ' isoforms, whereas the nuclear-cytoplasmic localization of the Acin1-L isoform was relevant to its SAP motif [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals have identified Acinus and Pinin as essential cellular components that bridge chromatin remodeling, transcription and splicing through the formation of analogous ASAP and PSAP complexes 14,16,17,48–51 . Sequence alignment and phylogenetic analysis show that the Arabidopsis orthologs, AtACINUS and AtPININ, share higher levels of sequence similarity to their animal counterparts than to each other and appear to have evolved independently since the separation of the plant and metazoan kingdoms 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Another RSB-containing protein, Pinin, forms a similar protein complex named PSAP, which has distinct biological functions 14,15 . The ASAP and PSAP complexes are believed to function at the interface between histone modification, transcription, and alternative splicing (AS) in metazoans 14,16,17 . In Arabidopsis , AtRNPS1, also known as ARGININE/SERINE-RICH 45 (SR45), has been implicated in splicing, transcription and RNA-dependent DNA methylation, with effects on multiple aspects of plant development as well as stress and immune responses 1823 .…”
Section: Introductionmentioning
confidence: 99%